An exploration of the application of universities as artificial institutional entrepreneurs: The case of China. Issue 1 (9th February 2018) - Zheng, Connie; Hu, Mei‐Chih
Abstract : Universities worldwide have increasingly been encouraged to incubate and create business enterprises in order to fulfil national and regional economic development objectives via rapid research commercialization, technology transfer, and open innovation. The definitions of university‐level entrepreneurship appear to be controversial in the extant literature, with special reference to government–university–industry partnerships under the overarching theoretical framework of institutional entrepreneurship. No longer do universities act only as agents for knowledge transmission and diffusion but also as business enterprises to help change formal institutional arrangements to meet evolving economic and social demands and to graft the entrepreneurial paradigm into academic culture and structures. As a transitional economy, have China's universities also acted as institutional entrepreneurs for change? In this paper, we address this research question by exploring the nature of government–university–industry links and the application of "institutional entrepreneurship" to Chinese universities. We use a case analysis of the Industry Technology Research Institute of Geo‐Resources and Environment Co. Ltd. established by the China University of Geosciences to support our argument that Chinese universities are artificial institutional entrepreneurs. As a result of our analysis, we identified several success factors and constraints on universities as institutional entrepreneurs in the context of China.